REFORMAS AL CODIGO TRIBUTARIO INSTITUYENDO QUE LO CONTENCIOSO TRIBUTARIO SE TRAMITE ANTE UN JUEZ DE PRIMERA INSTANCIA Y QUE EL TRIBUNAL CONTENCIOSO TRIBUTARIO SEA JUEZ DE SEGUNDA INSTANCIA, PARA MATERIALIZAR EL ART. 86, REGLA 3, INCISO 2° DE LA CONSTITUCIÓN - JARAMILLO QUEZADA, PEDRO ALEXIS (2015)
This research in the tax system has a special problem, which is the Contentious tax controversies, that having the proceedings in a single instance and the Constitution establishes the right of appeal of any decision. In the development of the research plan has sought to get to the problem based on a table of contents that relate to tax procedural law. The framework supports the understanding of the main institutions of the tax regime as well as the evolution of this until now and set the objectives of the tax practice of forensic solving skills. The Constitution as supreme law allows the analysis of the guarantees of taxpayers in the subjects of disputes and in the Organization of the State judiciary, which is the Court of the contentious tax for this study is weighted. Explores the management of the tax administration on the determination and collection of obligations that generate complaints and are used to find the actions that conduct tax contentious. To find our proposal has been treated the claim administrative and tax litigation judgment with all its effects highlighting phases, which passes through this process that consists of the performances of the litigants and the judges stressing the limitation as to get to the next level or second-instance procedure. - 5 - The opinion survey has contributed to reinforce our proposal or in essence of the reform of the tax code by establishing two instances for processing. The conclusions and recommendations as well as the legal proposal are the product of the study of the problem and possible solutions.